Relationship between running kinematic changes and time limit at vVO2max. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p428 - Sebastião Iberes Lopes Melo; Leonardo De Lucca (Universidade Federal de Santa Catarina, 2012)
DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p428Exhaustive running at maximal oxygen uptake velocity (vVO2max) can alter running kinematic parameters and increase energy cost along the time. The aims of the present study were to compare characteristics of ankle and knee kinematics during running at vVO2max and to verify the relationship between changes in kinematic variables and time limit (Tlim). Eleven male volunteers, recreational players of team sports, performed an incremental running test until volitional exhaustion to determine vVO2max and a constant velocity test at vVO2max. Subjects were filmed continuously from the left sagittal plane at 210 Hz for further kinematic analysis. The maximal plantar flexion during swing (p<0.01) was the only variable that increased significantly from beginning to end of the run. Increase in ankle angle at contact was the only variable related to Tlim (r=0.64; p=0.035) and explained 34% of the performance in the test. These findings suggest that the individuals under study maintained a stable running style at vVO2max and that increase in plantar flexion explained the performance in this test when it was applied in non-runners.